Distributing Knowledge - Heller, Richard | https://orcid.org/0000-0003-3161-5967 (Open Book Publishers, 2026)
Inequity is deeply embedded in higher education: in who can access learning, whose knowledge is created and valued, who gets published, and who ultimately benefits from universities’ work. Distributing Knowledge argues that the sector is falling short of its public mission—and that incremental reform is no longer enough.Drawing on research, policy analysis, and real-world examples from across the globe, Richard Heller presents a compelling case for a distributed model of higher education designed to promote knowledge equity. The book shows how corporatisation, managerialism, and commercial control of educational technology and academic publishing have narrowed participation, reinforced global inequalities, and weakened universities’ ethical foundations. At the same time, it highlights the opportunities offered by digital technologies, Open Education, and collaborative knowledge creation to reverse these trends.This volume introduces a practical framework for distributing knowledge more equitably—across its creation, publication, and delivery—grounded in core values of justice, autonomy, sustainability, and public good. It explores how open publishing, Open Educational Resources and Practices, distributed education structures, inclusive research practices, and supportive decentralised digital infrastructure can widen access, reduce carbon footprints, and amplify under-represented voices. Each chapter concludes with concrete steps to guide institutions, policymakers, and educators towards meaningful change.Ultimately, this book is both a critique and a call to action. It challenges universities to re-imagine their role in society and offers a realistic pathway for transforming higher education into a more ethical, inclusive, and sustainable system—one capable of distributing knowledge in ways that genuinely reduce inequity and respond to the urgent challenges of our time.